Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan pada Sektor Basic Materials di BEI Periode 2020-2023 - Kartika Kartika; Artie Arditha Rachman; Arif Makhsun (CV. Ulil Albab Corp, 2024)
This study aims to answer the question, “How do financial performance metrics such as CR, DAR, DER, TATO, FAT, ROA, and ROE affect firm value as measured by PCV?” by analyzing the relationship between these ratios and firm value. This study used purposive sampling to collect data from seventeen raw material companies listed on the IDX, with a total of sixty-eight observations. The data analysis process used SPSS version 26 software and multiple linear regression. Firm value was found to be influenced by CR, DAR, DER, TATO, FAT, ROA, and ROE.